Applications of Chitosan Coating to Extend Shelf-Life of Snakefruits (Salacca zalacca) - Apriliyanti, Erwidia Dwi; Purbasari, Dian (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
Snakefruit (Salacca zalacca) is a horticultural plant native inIndonesia with a short shelf life. Factors affecting salak fruit's shelf life are microorganism contamination, respiration rate, and high transpiration. This study aims to determine the effect of chitosan coating on quality characteristics in increasing the shelf life of salak fruit. This study used a completely randomized design (CRD) with two factors: differences in chitosan concentration and storage time at room temperature. The data were analyzed using an ANOVAtwomix factor witha test (α = 0,05), ifit was found to be significantly different, Duncan's further test was carried out. The results showed the lowest weight loss at 1% chitosan concentration was 10,8628%, the highest hardness was at1% chitosan concentration at 0,0971 N/mm2, the highest L value at 1% chitosan concentration was 42,1744, the highest a value was at concentration 0,5% chitosan was 3,8944, the highest b value at 1% chitosan concentration was 9,7122 and the lowest Total Dissolved Solids (TPT) was at 1,5% chitosan concentration at 17,7000°brix.